2009
DOI: 10.1111/j.1471-0528.2009.02190.x
|View full text |Cite
|
Sign up to set email alerts
|

Misoprostol for second trimester pregnancy termination in women with prior caesarean: a systematic review

Abstract: Background Second trimester pregnancy induction with misoprostol in women with prior caesarean delivery is not well studied.Objective To estimate the risk of uterine rupture using misoprostol as an induction agent for pregnancy termination in the second trimester of pregnancy in women with prior caesarean delivery.Search strategy Cases of women with a history of prior caesarean delivery and subsequent misoprostol induction for pregnancy termination in the second trimester (16-28 weeks) were obtained from two m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(67 citation statements)
references
References 32 publications
5
58
0
4
Order By: Relevance
“…Medical induction has become the mainstay in the management of second trimester abortion [1,2]. Reasons for this include the non-requirement of anesthesia or a skilled operator, and the abortus is usually delivered intact which aids in genetic diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Medical induction has become the mainstay in the management of second trimester abortion [1,2]. Reasons for this include the non-requirement of anesthesia or a skilled operator, and the abortus is usually delivered intact which aids in genetic diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…The safety and efficacy of misoprostol in second trimester termination of pregnancy in patients with previous cesarean section have been documented in various studies [11,12]. In our study, five patients had delivery by cesarean section in previous pregnancy.…”
Section: Second Trimester Abortionmentioning
confidence: 75%
“…The pregnancies less than 20 weeks had a higher rate of incomplete abortion and surgical intervention as compared to pregnancies greater than 20 weeks in our study. Uterine rupture is a rare but serious complication of medical induction of abortion in the second trimester of pregnancy, especially in women with a previous uterine scar (20). Although prior hysterotomy is suspected to be a risk factor for uterine rupture during labour induction abortion, approximately one-half of uterine ruptures occur in unscarred uteri.…”
Section: Discussionmentioning
confidence: 99%
“…This review showed that the uterine rupture rate for women with one prior low transverse caesarean birth and subsequent second trimester misoprostol termination was 0.28%. The other current meta-analysis included 12 studies and 461 patients revealed that the uterine rate among women with one prior low transverse caesarean birth was 0.43% during second trimester pregnancy termination (20). The lowest total misoprostol dose administered prior to uterine rupture was a single dose of 200µg (22), but several women received multiple doses prior to uterine rupture.…”
Section: Discussionmentioning
confidence: 99%